“Obtención de la almendra de la nuez del marañón (anacardium occidentale L.) y su conservación por frito – salado” - Pezo Gonzales, Mario (1994)
This study was based on search methods suitable for the obtaining of the cashew almond (Anacardium occidenta1ª.) (L), working with the variety own of the area u "native", determining is its features phytosanitary, physical, values unit and the composition chemical, allowing this evaluation characterize the matter prima. The work was developed in three stages: treatment of the raw, extraction of Walnut almond and almond obtaining frito-salado as a final product. Fritas-saladas almonds, a differential test of sensory evaluation was to determine the proper salty. Also the physico-chemical analysis was performed and, finally, determined the adsorption isotherm and the evaluation of 4 flexible packaging, during storage. The processing of the raw material is: the greatest amount of whole almonds is obtained with treatment of remoistening, prior to roasting and shelling, d...